A pedagogia histórico-crítica e a formação do sujeito professor crítico. - Antes, Gilberto (2020)
This study aimed to build an understanding and discussion about the processes of subjectification in the constitution/construction of the subject, and especially with regard to the critical teacher, by means of social discourses, but specifically through the Historical-Critical Pedagogy from Dermeval Saviani’s work, a pedagogy which has been carried out systematically in the State of Paraná in the last few decades. By building a theoretical methodological analysis through a post-structuralist view, in particular from the perspective of Michel Foucault’s work, we sought to go over this and discuss the processes of subjectification of the subjects, within a new social, political, economic and cultural reality, which we call postmodern or postmodernity. This society has created a series of mechanisms, devices and technologies that aim to reach individuals in several ways, creating a power relations network, or micropower, which permeate individuals, surrounding them, with the aim of producing or shaping them, turning them into subjects of these devices, according to a specific objective of being and acting in their positioning and visions towards the world. By using this poststructuralist view and the Foucauldian approach, we analyzed Dermeval Saviani’s pedagogic proposal, understanding that this kind of pedagogy can be understood as a social discourse, one of these devices, among many others, that seeks the formation of a certain type of subject, and in particular with regard to the teacher’s model, critical, transformer and aware of their reality, which the pedagogy aims to form, in order to achieve its purposes of transforming the social reality of society through education. From this point of view, we got inspired by the poststructuralism and used the resources provided by Michel Foucault’s work to carry out a discourse analysis of the Historical-Critical Pedagogy, where we looked for a discussion regarding the processes of subjectification of the subjects to understand how these processes take effect and what resources are used in order to reach individuals and turn them into subjects of theses discourses. Thus, we used the Historical-Critical Pedagogy and its effectuation processes, understanding that this proposal presents itself as one of these discourses that aim at the formation of a certain type subject, with patterns of being and acting before the world. Seeking a better understanding of these subjectification mechanisms of the subjects, we sought to create ways of resistance, for society to build and respect freedom among subjects, and that not even an idea or perspective becomes hegemonic and diversity is ensured for subjects and respected.